Compared to Fishmeal, Dietary Soybean Meal Improves the Reproductive Performance of Female Yellow Catfish (Pelteobagrus fulvidraco) Broodstock. (20th April 2023) - Chen, Zheng; Fei, Shuzhan; Liu, Cui; Duan, Yuanhui; Liu, Haokun; Han, Dong; Jin, Junyan; Yang, Yunxia; Zhu, Xiaoming; Xie, Shouqi
Abstract : To investigate the effects of different dietary protein sources on the reproductive performance of female broodstock, yellow catfish ( Pelteobagrus fulvidraco ) were fed with three experimental diets using fishmeal (FM), soybean meal (SBM), and rapeseed meal (RSM) as main protein sources, respectively. Females (initial weight: 64.56 ± 0.45  g) were distributed into 9 net cages for feeding trial. Results indicated that 30% dietary SBM improved the reproductive performance for higher gonadosomatic index (GSI), relative fecundity, total egg production, egg diameter, and hatching rate. In addition, SBM and RSM diets resulted in higher estradiol (E2), vitellogenin (VTG), luteinizing hormones (LH), and lower follicle-stimulating hormone (FSH) and testosterone (T) in plasma (P < 0.05 ) of female broodstock. Dietary SBM and RSM also resulted in lower mesenteric fat index (MFI), plasma total cholesterol (TC), plasma total bilirubin (T-Bil) contents, and gonadal cortisol concentrations, while dietary SBM downregulated the transcription levels of steroidogenesis-related proteins by negative feedback (P < 0.05 ). The results demonstrated that dietary SBM and RSM could promote sex steroid hormone and VTG biosynthesis and showed hypocholesterolemic effects. Besides, 30% dietary SBM inclusion could improve the reproductive performance of female yellow catfish broodstock.